2016
DOI: 10.1111/iep.12208
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to ethinylestradiol increases ventral prostate growth and promotes epithelial hyperplasia and inflammation in adult male gerbils

Abstract: The aim of this study was to analyse morphologically the ventral prostate of adult Mongolian gerbils exposed to ethinylestradiol (EE) during the first week of postnatal development. Lactating females received daily, by gavage, doses of 10 μg/kg of EE diluted in 100 μl of mineral oil from the 1st to 10th postnatal day of the pups (EE group). In the control group (C), the lactating females received only the vehicle. Upon completing 120 days of age, the male offspring were euthanized and the prostates collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…ethinylestradiol on the prostate of gerbils (Falleiros-Junior et al, 2016), indicating an important role of AR in the synergistic effect of estrogen and androgen on the prostate. Low-dose BPA might bind to AREs and activate the existing AR to improve its response ability to low-level androgen (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ethinylestradiol on the prostate of gerbils (Falleiros-Junior et al, 2016), indicating an important role of AR in the synergistic effect of estrogen and androgen on the prostate. Low-dose BPA might bind to AREs and activate the existing AR to improve its response ability to low-level androgen (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Studies indicated that BPA could induce ERα upregulation, which related to prostate cell proliferation (Huang et al, 2017) and prostate hyperplasia (Campos et al, 2015). AR in prostate was usually increased by low-dose E 2 and DES treatments (Falleiros-Junior et al, 2016; Nonneman et al, 1992) and decreased by a high concentration of estrogen (Prins and Birch, 1995). Hence, the range of E 2 /T ratio was critical for the expression of AR.…”
Section: Discussionmentioning
confidence: 99%
“…As in the adult male prostate, we also observed an increase in epithelial compartment volume, epithelial height, and thickness in smooth muscular layer. Neonatal exposure to estrogen is associated, in adult life, with the onset of prostatic disorders, such as inflammation and premalignant lesions (Coffey and Buchanan 2001; Prins et al, 2001; Perez et al, 2011; Falleiros‐Júnior et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The stromal remodeling may have been caused by an increased recruitment of macrophages, especially in the stroma, where this cell type can secrete different chemical and enzymatic mediators, actively participating in tissue remodeling (Silva et al, 2018), such as extracellular matrix metalloproteinases of types 2 and 9, as observed in prostate cancer in mice (Fang et al, 2013), in altered prostate tissue of male and female gerbils (Rochel‐Maia et al, 2011) and tissue remodeling in models with hydroxyapatite grafting, or in periodontal lesions (Carneiro et al, 2009; Zambuzzi et al, 2009). According to Falleiros‐Junior et al (2016), exposure to EE during the neonatal period promotes an increase in morphological alterations, such as foci of epithelial hyperplasia associated with inflammations in the stromal and luminal compartments of the ventral prostate of adult gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogenic activity can also be shown with the use of synthetic estrogens, such as ethinylestradiol (EE), used as a contraceptive and in hormonal therapies, widely dispersed in the environment due to its low degradation [54]. Falleiros-Júnior et al [55] and Perez et al [56] showed that both neonatal (10 μg/kg) and pubertal exposure (15 μg/ kg), respectively, promote repercussions on the adult prostate. Both studies reported the presence of hyperplastic areas associated with stromal and luminal inflammatory foci.…”
Section: Prostate Inflammation Induced By Edcs and Cell Adhesionmentioning
confidence: 99%